Vliv chronicky podávaných subletálních dávek parakvatu na délku telomer a rezistenci vůči oxidačnímu stresu drozofily - Tomášková, Jindřiška (Jihočeská univerzita, 2017)
As the most widely dispersed fauna around the world, insects are exposed to a range of stresses within their environments. Oxidative stress causes a disturbance of the balance between production of free radicals and antioxidant response, which leads to various physiological changes in an organism. Despite this, there are several of defense mechanisms, which include in particular the main antioxidant enzymes AKH. In this thesis, I tried to contribute especially to understand the physiological nature of telomere elongation after exposure to free radicals.
Effect of chronic sublethal paraquat doses on telomere length and resistance to oxidative stress at Drosophila
Keywords: oxidativní stres; volné radikály; antioxidační odpověď; antioxidační enzymy; oxidative stress; free radicals; antioxidant response; antioxidant enzymes